Klebsiella ozaenae Bacteremia in a Kidney Transplant Recipient. (28th April 2013) - Kumar, Shree; Alfaadhel, Talal; AlBugami, Meteb M.
Abstract : Infections remain a dreadful complication after solid organ transplantation. Almost all microorganisms could cause this complication, including unusual ones. We report a 73-year-old patient, with a history of kidney transplant for 38 years on minimum immunosuppression, who presented with high-grade fever and gastrointestinal symptoms. Klebsiella ozaenae was isolated from blood cultures. She had a prompt response to antibiotics and recovered completely in a short period. Subsequent evaluation of her nasal cavity and sinuses did not show any abnormalities. Klebsiella ozaenae is primarily a colonizer of the oral and nasopharyngeal mucosa, which does not usually cause severe infections. Only 12 cases of Klebsiella ozaenae bacteremia have been reported, none of them in the context of solid organ transplant recipient.